Foreign bodies in unusual sites in ENT: two case report - Behera, Sanjaya Kumar; Aparoopa, Ananya; Behera, Saroj Kumar; Jena, Anita Manjari (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
In otorhinolaryngology practice, foreign body impaction in the ear, nose, and throat areas and in the head and neck are emergencies. Here we present two unusual cases that we treated at our District Headquarter Hospital. First case involved a metallic foreign body a key ring in the oropharynx extending into the nasopharynx and laryngopharynx in a child, and the second case involved a foreign body wooden stick accidentally penetrating the postauricular region across the cheek to the zygomatic arch near lateral margin of periorbital area causing grade III facial nerve paresis in a female. We successfully removed both the foreign bodies. In first case after the removal of metallic foreign body from throat we kept patient for nasogastric feeding for 48 hours followed by normal liquid diet. In Second case after removal of foreign body the residual facial nerve paresis was resolved with tapering dosage of steroid.